Sentidos atribuídos pelos docentes da graduação em enfermagem da Universidade Regional do Cariri (URCA) ao conceito de integralidade do cuidado e sua correlação com a formação em saúde - Pinho, Aline Samara Dantas Soares [UNIFESP] (2010)
The education of health professionals, according to official documents that give directions to its political, ideological, technical and scientific guidance, is supposed to be compatible with the Brazilian National Health Care System (SUS) consolidation process. In addition, it should be guided by the principle of health integrality as a right granted by citizenship and the principle of dignity that should be granted to the persons in need of health care. By considering the central role played by professors within the formal education scenario, it is fundamental to understand the sense it imprints upon the concept of integrality, in the perspective of developing pedagogical practices required for the formation of future nursing professionals. With objective of identify the senses ascribed by nursing undergraduate faculty members of Universidade Regional do Cariri (Regional University of Cariri – URCA) concerned with the concept of integrality and its correlation with health education. The research evolved from a literature review on the theme by using interviews (either one-to-one or in groups) with professors representing course disciplines whose credit hours are also developed in health services (supervised internship programs), where they act as preceptors. The analytical reference in use was the approach focused on the production of daily life senses and discourse practices under a constructionist standpoint. Two main theme blocks were adopted to systematize the collected empirical material. They were labeled “INTEGRALITY/IDEALITY” and “INTEGRALITY IN REALITY”. The former refers to an “idealized”, purely “discourse” integrality (which reproduces the principles of SUS and is synonymous with holistic attention and interdisciplinary action within the context of health care and the teaching of the nursing profession), whereas the latter allows characterizing “integrality” in its concrete planning and operation of services, whose organizational and operative features (fragmentation and discontinuity of health care; emphasis on procedure production, etc.) lead to remarkable (negative) implications for the education of nurses within the scope of graduation, undermining the ideal of integrality as proclaimed by the first theme block. It is possible to say that the study featured an INVERTED MIRROR IMAGE between what is perceived in the “integrality/ideality” and the “integrality”/reality, i.e., the real features found by professors in health service planning and operation that can be used as fields of practice for their students. The study was able to advance a little beyond the formal, quite idealized discourse of professors about the sense of integrality as it attempted to locate such discourse in the complexity (and challenge) of fulfillment within the context of concrete institutional practices produced by SUS. The study also led to a constructionism-oriented practice from the meeting of researcher and professors, which, by thinking over their experiences and difficulties, seems to point to (and place a bet on) new possibilities of meeting and reflection, as much as to produce professor-care practices committed with health care integrality and with a radical ethics towards the defense of life.